Palbociclib plus letrozole versus placebo plus letrozole in Asian postmenopausal women with oestrogen receptor–positive/human epidermal growth factor receptor 2–negative advanced breast cancer: Primary results from PALOMA-4. (November 2022) - Xu, Binghe; Hu, Xichun; Li, Wei; Sun, Tao; Shen, Kunwei; Wang, Shusen; Cheng, Ying; Zhang, Qingyuan; Cui, Shude; Tong, Zhongsheng; Geng, Cuizhi; Song, Erwei; et al.
Abstract: Background: The cyclin-dependent kinase 4/6 inhibitor palbociclib has demonstrated efficacy and a manageable safety profile in combination with endocrine therapy in women with oestrogen receptor–positive (ER+)/human epidermal growth factor receptor 2–negative (HER2–) advanced breast cancer (ABC) in international phase 3 trials. The phase 3 PALOMA-4 trial evaluated the efficacy and safety of palbociclib plus letrozole versus placebo plus letrozole in Asian women with ER+/HER2– ABC. Methods: Postmenopausal women (n = 340) with no prior systemic treatment for advanced disease were randomised 1:1 to palbociclib (125 mg/d orally; 3 weeks on, 1 week off) plus letrozole (2.5 mg/d orally; continuously) or placebo plus letrozole. The primary end-point was investigator-assessed progression-free survival (PFS). Secondary end-points included tumour response and safety. Results: Median (95% CI) PFS was 21.5 (16.6–24.9) months with palbociclib plus letrozole and 13.9 (13.7–16.6) months with placebo plus letrozole (hazard ratio, 0.68 [95% CI, 0.53–0.87]; P = 0.0012). Consistent with the established safety profile, the most common adverse events (AEs) with palbociclib plus letrozole were neutropenia, leukopenia, thrombocytopaenia, and anaemia. Grade 3/4 neutropenia was reported in 84.5% of patients in the palbociclib arm versus 1.2% in the placebo arm. One serious AE of febrile neutropenia in the palbociclib group was reported. Conclusions: Findings from PALOMA-4 support the efficacy and safety of first-line palbociclib plus letrozole in postmenopausal Asian women with ER+/HER2– ABC. No new safety concerns of palbociclib plus letrozole were identified. Trial registration: Clinicaltrials. gov, NCT02297438. Highlights: Addition of palbociclib to letrozole prolonged PFS in Asian women with ER+/HER2– ABC. No new safety concerns of palbociclib plus letrozole were identified in Asian women. Findings support first-line palbociclib in postmenopausal Asians with ER+/HER2– ABC.